SURVIVAL STRATEGIES OF SMALL TOURISM BUSINESS FACING THE COVID-19 PANDEMIC IN AMED KARANGASEM, BALI (JURNAL KEPARIWISATAAN, 2023)
This study aims to determine the strategy of tourism business actors in Bali's Amed Karangasem area to run their business during a pandemic. Data was obtained by conducting in-depth interviews and distributing questionnaires to tourism business actors. Results of data analysis showed that employers will continue to do the same business by reducing employees. There are also layoffs of employees, salary cuts, and significant discounts to customers to be able to get through the pandemic. Business actors will change their business strategies. Tourism businesses in Amed are faced with financial problems. The most significant financial issues during the pandemic are not being able to pay salaries/wages (66.7%), debt payments (20%), bill costs and other financial problems (13.3%). The implication of this study is to design more resilient business strategies that will help small business owners in the tourism sector in Amed Bali survive future crises. This study’s theoretical implications contribute to our understanding of how small tourism businesses respond to crises and government policies. In contrast, its practical implications offer actionable recommendations to improve the resilience and support for businesses in the Amed region and potentially in similar tourism-dependent areas.